Kajian Penerapan Teknologi Cerdas dalam Sistem Multi-Lane Free Flow (MLFF) Pada Jalan Toll Trans Sumatera - Winanti, Lisa Ayu; Fitriani, Heni (Universitas Muhammadiyah Palembang, 2025)
Queues at toll gates remain a major problem on highways. This often causes congestion when approaching the toll gates, as the number of incoming vehicles exceeds the existing service capacity. The Indonesian government will implement a Multi-Lane Free Flow (MLFF) system as a solution so that toll road users do not need to stop their vehicles when making toll payments. However, the government needs to further investigate the problems that may arise from eliminating queues, such as changes in traffic characteristics and vehicle arrival times at major toll road intersections. This study examines the implementation plan and attempts to identify potential problems when MLFF is implemented. It also examines how to maintain these positive impacts so that the toll road can meet minimum service standards. This study uses forecasting or time series methods for traffic occurrences, taking into account service times, queuing systems, and gate capacity. This study also considers the project's financial feasibility based on toll revenues and a cost-benefit analysis of the toll road. Based on the results of this study, it can be concluded that the implementation of the MLFF system at the Keramasan toll gate is feasible from a physical and financial perspective. However, in the transition process, good socialization is needed from the government and toll road investors, as well as public acceptance of the MLFF system or this new payment transaction.